2014
DOI: 10.1186/1471-2164-15-898
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale transcriptome comparison reveals distinct gene activations in wheat responding to stripe rust and powdery mildew

Abstract: BackgroundStripe rust (Puccinia striiformis f. sp. tritici; Pst) and powdery mildew (Blumeria graminis f. sp. tritici; Bgt) are important diseases of wheat (Triticum aestivum) worldwide. Similar mechanisms and gene transcripts are assumed to be involved in the host defense response because both pathogens are biotrophic fungi. The main objective of our study was to identify co-regulated mRNAs that show a change in expression pattern after inoculation with Pst or Bgt, and to identify mRNAs specific to the fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
149
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 43 publications
17
149
0
Order By: Relevance
“…6). Likewise, we found that R, G, replication, recombination and repair (L), transcription (K), signal transduction mechanisms (T) and E were the main functional categories in the previous RNA-seq data [7]. However, only a few protein-species were detected in the DNA replication and transcription, nucleotide excision repair and signal transduction pathways in proteomic analysis.…”
Section: Functional and Bioinformatics Analysismentioning
confidence: 53%
See 2 more Smart Citations
“…6). Likewise, we found that R, G, replication, recombination and repair (L), transcription (K), signal transduction mechanisms (T) and E were the main functional categories in the previous RNA-seq data [7]. However, only a few protein-species were detected in the DNA replication and transcription, nucleotide excision repair and signal transduction pathways in proteomic analysis.…”
Section: Functional and Bioinformatics Analysismentioning
confidence: 53%
“…The transcriptome data were obtained with the same experimental design in our previous study [7]. In the correlation analysis, we calculated the Pearson correlation coefficient (r), and divided the transcript/protein pairs into two groups based on their up-or down-accumulation of protein expression abundances (Supplementary Table 5).…”
Section: Correlation Analysis Between Protein and Mrna Expression Promentioning
confidence: 99%
See 1 more Smart Citation
“…tritici (Bgt) and Puccinia striiformis f. sp. tritici (Pst), separately (Zhang et al, 2014b). The RNA seq data was generated in triplicates and expression was calculated using Trinity package as described (Haas et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The unavailability of genomic information, composite nature of genome and complexity in application of modern functional genomics tools could be the probable reason for the same. In recent years, the genome sequence and numerous development and stress related high throughput RNA sequence data have been available from T. aestivum (IWGSC, 2014; Zhang et al, 2014b, 2016; Liu Z. et al, 2015; Pingault et al, 2015), which enabled the genome wide characterization of various gene families (Shumayla et al, 2016a,b; Zeng et al, 2016). Since the CaCA proteins are involved in several vital functions from development to stress response, there characterization becomes essential in an important food crop like T. aestivum .…”
Section: Introductionmentioning
confidence: 99%